2020
DOI: 10.1109/access.2020.3027497
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Domain Adversarial Self-Calibration for Electromyography-Based Gesture Recognition

Abstract: Surface electromyography (sEMG) provides an intuitive and non-invasive interface from which to control machines. However, preserving the myoelectric control system's performance over multiple days is challenging, due to the transient nature of the signals obtained with this recording technique. In practice, if the system is to remain usable, a time-consuming and periodic recalibration is necessary. In the case where the sEMG interface is employed every few days, the user might need to do this recalibration bef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…Zhang J. et al ( 2019 ) developed DBN to deal with the non-linear and time-varying properties of sEMG signal, and proved the potential of DBN through the measured data. Although one of the advantages of unsupervised learning is that it eliminates the need for manual tagging, self-training strategy is likely to increase classification errors, especially with data distribution mutation (Huang et al, 2017 ; Côté-Allard et al, 2020 ).…”
Section: Pattern Recognition-based Semgmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang J. et al ( 2019 ) developed DBN to deal with the non-linear and time-varying properties of sEMG signal, and proved the potential of DBN through the measured data. Although one of the advantages of unsupervised learning is that it eliminates the need for manual tagging, self-training strategy is likely to increase classification errors, especially with data distribution mutation (Huang et al, 2017 ; Côté-Allard et al, 2020 ).…”
Section: Pattern Recognition-based Semgmentioning
confidence: 99%
“…TDNN processing of combined with sEMG and kinematics data could show excellent performance in the prediction of simultaneous motion of shoulder joint and elbow joint (Kwon and Kim, 2011 ; Blana et al, 2016 ; Day et al, 2020 ). Since the quantity of training datasets in DL affects the performance of the model, the limited datasets collected from multiple topics should be first extend by certain data-augmentation approaches that can also enhance the robustness of the model (Tsinganos et al, 2018 ; Yang et al, 2018 ; Côté-Allard et al, 2020 ). Moreover, due to the nature of the training in a neural network, the process of transfer learning is very straightforward (Yosinski et al, 2014 ; Côté-Allard et al, 2019 ).…”
Section: Pattern Recognition-based Semgmentioning
confidence: 99%
“…Some of these studies addressed electrode shifts and day-to-day variability through adaptive transfer learning [24], [25], intersession gesture recognition using deep domain adaptation on unlabeled test data or fine-tuning labeled calibration data [26], and periodic recalibration for multiple days use for prosthetic control by applying transfer learning with few training data [27]. Furthermore, a recent study showed that aggregating source distributions from multiple users with deep transfer learning in gesture recognition enhanced model performance [28]. Since an FMG signal has similar characteristics, multiple domain adaptation was investigated with the traditional ML algorithm in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In our prior work, the pooled-variance of subjects was used to create a subject-general model (one model trained and used by many subjects) that exceeded the accuracy of traditional within-subject models (one model for each subject). We have also validated it in the presence of confounding factors, such as inter-session and across day variations, using self-calibration (Côté-Allard et al, 2020b ). In these works, however, each of the test users supplied a full training set, resulting in little benefit to the training burden.…”
Section: Introductionmentioning
confidence: 99%